Four women at a y-Walk party - Unknown:::Creator::::::::::::
Photograph shows four women standing and smiling at a y-Walk party. The party is probably at D.B. Cooper's in San Jose. Two of the women are wearing y-Walk stickers on their clothing and there is a bouquet of y-Walk balloons behind them. There is a banner partially visible above them that reads: "D.B. Cooper's, M" and a fifth woman is barely visible in the background.